P273 The duration of clinical remission in patients with Crohn's disease depends on the frequency of administration of mesenchymal stromal cells of the bone marrow. (27th May 2021) - Knyazev, O; Kagramanova, A V; Lishchinskaya, A; Li, I; Shkurko, T; Veselov, A; Fadeeva, N; Zhulina, E; Parfenov, A
Abstract: Background: Anti-cytokine therapy with anti-TNF-α drugs contributes to the achievement of persistent remission of Crohn's disease (CD). Allogeneic mesenchymal stromal cells (MSC) of the bone marrow are also used for the treatment of CD. Objective: to evaluate the duration of remission of CD in the context of mesenchymal stromal cells (MSC) therapy of the bone marrow, depending on the frequency of MSC administration. Methods: 76 patients with CD with luminal form of CD (terminal ileitis, colitis, and ileocolitis) were divided into two groups. The first group of patients aged 19 to 58 years (Me-29) (n=34) received culture of MCS according to the scheme: 0-1-2-12-26-52 weeks, then annually 2 times a year. The second group of patients with CD (n=42) aged 20 to 62 years (Me-28) received culture of MCS according to the scheme: 0-1-2-12-26-52 weeks to achieve remission within one year. The effectiveness of therapy was evaluated 12, 24, 36, 48 and 60 months after the start of therapy using the Harvey-Bradshaw index. Results: During 12 months of follow-up, 4/34 patients (11.76%) relapsed among patients in 1-st group. In 2-nd group, relapse occurred in 5/42 (11.9%) (HR-0.63; 95% CI 0.288-3.397; p=0.84). After 24 months, 6/34 patients (17.6%) relapsed in 1-st group. In the 2-nd group of patients, the disease relapsed in 11/42 (26.2%) (HR-0.674; 95% CI 0.278-1.634; p=0.37). After 36 months, the disease relapsed in 7/34 patients in 1-st group (20.6%). In the 2-nd group, relapse was in 18/42 (42.8%) (HR-0.48; 95% CI 0.228-1.014; p=0.038). After 48 months, in the 1-st group receiving MSCS, a relapse occurred in 9/34 (26.5%). In the 2-nd group, relapse occurred in 22/42 (52.4%) (HR-0.5; 95% CI 0.269-0.949; p=0.021). After 60 months, 10/34 (29.4%) relapsed in 1-st group. In the 2-nd group, relapse occurred in 24/42 (57.1%) (HR-0.463; 95% CI 0.250-0.860; p=0.007). Conclusion: The duration of clinical remission in patients with luminal Crohn's disease depends on the frequency of administration of mesenchymal stromal cells.